Pseudohypercreatininemia after surgery for aortic dissection: a case report - Ayako Tasaki; Makoto Fukuda; Yuki Ikeda; Masatora Yamasaki; Ikko Yamaguchi; Shinichi Aishima; Motoaki Miyazono (BMC Nephrology, 2023)
Abstract Background Elevated creatinine concentrations often indicate acute renal injury and renal biopsies are considered in this situation. However,pseudohypercreatininemia is potential cause of elevated creatinine concentrations, and invasive interventions should be avoided. Case presentation A 54-year-old woman underwent surgery for descending aortic dissection.Nine days postoperatively, her creatinine concentration increased from 1 mg/dl to 5.78 mg/dl (normal range, 0.47–0.7 mg/dl). Azotemia and hyperkalemia were absent and physical examination findings were unremarkable. Cystatin C concentration was 1.56 mg/l (normal range, 0.56–0.8 mg/l) and pseudohypercreatininemia was suspected. Testing with different reagents showed a creatinine concentration of 0.84 mg/dl. Immunoglobulin (Ig)G was markedly elevated, and creatinine and IgG fluctuated in parallel, suggesting the cause of the pseudohypercreatininemia. IgG4 was also elevated at 844 mg/dl. Immunosuppressive steroid therapy effectively decreased the IgG concentration and resolved the pseudohypercreatininemia. Conclusions In cases of elevated creatinine concentration with the presence of abnormal proteins, pseudohypercreatininemia should be considered. We report a rare case of pseudohypercreatininemia caused by polyclonal IgG.